Blastulation rates of sibling oocytes in two IVF culture media: an evidence-based workflow to implement newly commercialized products. Issue 2 (February 2021) - Fabozzi, Gemma; Albricci, Laura; Cimadomo, Danilo; Amendola, Maria Giulia; Sanges, Federica; Maggiulli, Roberta; Ubaldi, Filippo Maria; Rienzi, Laura
Abstract: Research question: An evidence-based novel commercially available continuous IVF culture medium in compliance with an efficient quality-management system is proposed. Design: Non-interventional study on sibling oocytes. Intracytoplasmic sperm injection cycles among women aged 42 years or younger that used ejaculated spermatozoa and retrieved four to eight oocytes were included. Sibling oocytes were randomized for culture in the novel Geri-medium or continuous single culture medium (CSCM). Primary outcome measure was blastulation rate per cohort of inseminated oocytes; 1182 oocytes were required to outline down to a 7% difference (power = 80%). Results: A total of 181 cohorts of sibling oocytes were included. Geri-medium ( n = 631 oocytes) and CSCM ( n = 643 oocytes) resulted in similar blastulation rates (mean ± SD: 42.8% ± 30.1% versus 43.1% ± 29.0%; Wilcoxon signed rank test = 0.77). Blastocysts cultured in the former ( n = 275 versus n = 277) showed longer timings during preimplantation development ( P < 0.01) and were poorer quality (26% versus 18%; P = 0.03). Euploidy rate was no different in cycles that underwent preimplantation genetic testing for aneuploidy ( n = 113) (117/237 [49%] versus 117/249 blastocysts [47%]; P = 0.6). Ongoing implantation rate was comparable in the study arms after euploid (29/47 [63%] versus 14/ 34 [41%]; P = 0.1) or untested (12/31 [39%] versus 7/18 [39%]; P = 0.3) transfers. Conclusion: Blastulation rate among cohorts of sibling oocytes cultured in the same incubator is a fast, reliable and comprehensive performance indicator to validate novel commercially available culture medium. The media tested were considered similarly efficient. The differences in blastocyst morphology and developmental timings warrant further investigation, although euploidy and ongoing implantation rates were similar.